(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: In this work, the optical and structural properties of an composite were studied, the optical properties were studied by the UV-Visible spectrophotometer technique, and the structural properties were studied by the Xray diffraction technique. Materials and Methods: Different amounts of silica nanoparticles (SiO2 NPs) were loaded onto a composite consisting of ultra-high molecular weight polyethylene oxide (UHMWPEO), copper nanoparticles (Cu NPs), and silver nanoparticles (Ag NPs), and silica was added in different amounts (0.05, 0.07 and 0.09 ) wt%.This work was carried out using the traditional casting method. Results: The results showed a good improvement in the optical and structural properties of the composite when it was loaded with silica nanoparticles. . Conclusion: In this study, we have successfully prepared and examined nanocomposite films with outside and inside SiO2 with a thickness of (75–85) μm. The optical properties improve by decreasing the energy gap from (3.95) eV to (3.78) eV. As for the structural properties, where X-ray diffraction tests showed an increase in the crystalline size of the composite films, it was found that the crystalline size increased from (32.1) nm to (33.7) nm. Silica nanoparticles affect the growth of the crystalline structure of the composite.